Effect of socioeconomic, nutritional status, diet, and oral habits on the prevalence of different types of malocclusion in school-children - Anand, Tanya; Garg, Arun K.; Singh, Swati (Acta Biomedica Atenei Parmensis, 2022)
Abstract Objective: Although there have been many reports on the prevalence of malocclusion, there is paucity of data concerning factors associated with it. The present study aimed to study the effects of three environmental factors namely socio-economic status (SES), nutritional status, and oral habits on malocclusion.Material and Methods:  A total number of 765 students [Low socio-economic status (LSS; 369 subjects) and High socio-economic status (HSS; 396 subjects)] based on Modified Kuppuswamy scale were examined within the age group of 13- 15 years amongst various government and private schools in Chandigarh, India. A questionnaire was filled up by the subjects, which was followed up with clinical examination using the Dental Aesthetic Index (DAI). Additionally, the provisional diagnosis, retained, transposed teeth, and overbite were estimated.Results: The total prevalence of malocclusion in the population was 49.7%. The prevalence of malocclusion in LSS was found to be 42.90% and in HSS was 57.10% (P: 0.003). The mean DAI score in LSS was 26.011 and in HSS was 27.179. The mean DAI score in soft eaters was 29.527, average eaters was 26.369 and hard eaters was 26.410.Conclusion: The total prevalence of malocclusion in Chandigarh was 49.7%. Class I type 1 was the most prevalent type of malocclusion. Adolescents belonging to HSS had more malocclusion as compared to those belonging to LSS. Soft diet caused increased malocclusion. The present study highlighted the effect of diet pattern on the prevalence of malocclusion. (www.actabiomedica.it)